Hedonism (Anandabad) in the perspective of Aesthetics along with it's realization and manifestation in Tagore's consciousness according to his music composition - A study/ নন্দনতত্ত্বের দৃষ্টিভঙ্গিতে আনন্দবাদ তথা রবীন্দ্র মননে আনন্দের উপলব্ধি ও বহিঃপ্রকাশ (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
In this article mainly two phrase are analyzed as a part of discussion like – How Hedonism (Anandabad) is analyzed in Aesthetic perspective and how ‘Ananda’ is established in ‘Tagore Songs’ with in its philosophical nature. Hedonism is a way of thinking in which the emotional feelings and linguistic expression of an individual’s mind about an object or an event can be connected to the external world with happiness and self-satisfaction. On the other hand, Art, sculpture, Music, Drama, Dance etc and the attempt to analyze all other human creations whether those are good or bad or beautiful or ugly, belongs to a part of Aesthetics which is called Soundarya Tattwa or Theory of beauty. Hence it can be said that the realizationn of “Beautifullness” leads to the transition to the happiness from the self satisfaction that human being can enjoy. Therefore in Aesthetics, Theory of beauty and Hedonism both are inter related. Different western philosophers have given different opinions about Hedonism (Anandabad) & Sense of beauty. For example, accordings to medival philosophers like St. Augustine and Thomas Aquinas, mysticism was interpreted in Aesthetic Theory. According to them there exists a divine beauty in the Universe and it is possible to get pleasure and happiness from that devine beauty and This joy & happiness pervades the living and inanimate elements of our entire Universe. So the world is blissfull. So it can be said that happiness is a internal feeling of human the gives peace to the mind. So in the first part of this article it has been briefly explained how Hedonism has been theoretically analyzed with the views of various philosophers mainly from the Aesthetic & Artitic point of view.           In the second part of this article, the forms of Joy (Ananda) in Tagore songs are analysed in the terms of Upa-parjay of ‘Ananda’ in the songs of Puja Parjay and songs of others ‘parjay’ of Gitabitan like Prakriti, Bichitra etc composed by him and also such songs addressing ‘Ananda’ in the dance drama has been discussed. Rabindranath was a worshiper of the ‘Brahma’ which is formless and in his intuition the supreme God is a super natural power that is called ‘Brahma’ and known s ‘Jivan Devta’ or ‘Antarjami’ to him who drives life from birth to death. So, Tagore perceived man, nature and God as the blissful entities of the universe. The essence of Tagore of indescribable joy and the mystery of the vision of religion. Therefore just as ‘Ananda’ has emerged as a Upa-parjay ‘Ananda in the songs of Puja Parjay of Gitabitan and songs of others ‘Parjay’ where Tagore has interpreted ‘Ananda’ as the Catalyst of the finite & infinite between God and liberation of life after death of human life from eternal world. Similarly in the other songs of other ‘Parjay’ of Gitabitan, except Puja, ‘Ananda’ or ‘Hedonism’ has come to the poet’s unique feelings & emotions. Which have been discussed with various example of Tagore songs in this part of this article.
Keywords: Hedonism Mysticism; sense of Beauty; Aesthics of beauty; Relationship of beauty & happiness; Supreme God as Jivandevata’; Songs of ‘Puja’ parjay; Upaparjay ‘Ananda’; Dance drama